Militær oppdragelse - Schaanning, Espen (Tidsskrift for kulturforskning, 2016)
Abstract After first giving an outline of the military practices and principles of Baden-Powell’s scout movement, I explore to what extent these practices and ideals were adopted by two Norwegian scout movements in the period from 1911 until the 1930s: Norske gutters spei-derkorps (NGS) and Norsk Speidergut-Forbund (NSF). As NGS was closed down rather quickly, I will finally dig deeper into the scout ideology of NSF. Based on official texts from NSF, especially Speidergutboken and the scout journal Speideren, I will argue that although NSF was a Christian organization and explicitly wanted to be anti-militaristic, it nevertheless adopted Baden-Powell’s military legacy: Not only was NSF organised in a military manner, using military practices and appealing to military ideals, but the military was also a constant field of reference in several ways.